The Relationship Between HbA1c Levels and the Severity of Erectile Dysfunction in Type 2 Diabetes Mellitus Patients at the Andrology Clinic of Dr. Ramelan General Hospital, Surabaya - Adinda Rifqi Faradila Tsany; Peter Gunawan Tandean; Prawesty Diah Utami; Jakaria Zansen (Universitas Airlangga, 2026)
Background: Type 2 diabetes mellitus (T2DM) can cause erectile dysfunction (ED) complications in the long term, the severity of which is considered important to correlate with blood glucose control, as measured by HbA1c levels.Objective: To determine the relationship between HbA1c levels and the severity of erectile dysfunction in T2DM patients at the Andrology Clinic of Dr. Ramelan General Hospital, Surabaya. Methods: Observational analysis using a cross-sectional approach, utilizing secondary medical record data from 25 patients during the period 2019–2024, in which the severity of ED was measured using the Erection Hardness Score (EHS) and analyzed using the Spearman's rank correlation test.Results: A total of 64% of patients were in the diagnostic range for diabetes, and there was a significant relationship between HbA1c levels and the severity of ED, as indicated by a p-value of 0.043 and a correlation coefficient of r=0.407 (moderate positive correlation).Conclusion: There is a relationship between HbA1c levels and the severity of erectile dysfunction, where a moderate positive correlation indicates that higher HbA1c levels are associated with lower severity or improvement of erectile dysfunction. The moderate strength of the correlation suggests that HbA1c is not the only factor influencing the occurrence of erectile dysfunction.